1992
DOI: 10.1111/j.1471-4159.1992.tb08451.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nerve Growth Factor and Nerve Growth Factor Receptor Genes in Human Tissues and in Prostatic Adenocarcinoma Cell Lines

Abstract: Nerve growth factor (NGF) mRNAs were detected and quantified in a variety of normal and neoplastic human tissues by northern blot hybridization. Human heart contained the highest NGF mRNA levels, whereas lower but comparable levels were found in the placenta, prostate, and kidney. All tissues examined coexpressed the low-affinity NGF receptor (LNGFR), whereas none of these tissues expressed the high-affinity NGF receptor encoded by the trk protooncogene. The widespread distribution of the LNGFR suggests that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 55 publications
2
69
0
Order By: Relevance
“…The SDS electrophoresis (data not shown) of the tumor-conditioned medium confirmed this assumption and demonstrated that one of them was NGF. Many kinds of tumors have been found secrete NGF, BDNF, NT-3, etc [26][27][28] . NGF high-affinity receptor TrkA was also found to exist in esophageal carcinoma [29] .…”
Section: Discussionmentioning
confidence: 99%
“…The SDS electrophoresis (data not shown) of the tumor-conditioned medium confirmed this assumption and demonstrated that one of them was NGF. Many kinds of tumors have been found secrete NGF, BDNF, NT-3, etc [26][27][28] . NGF high-affinity receptor TrkA was also found to exist in esophageal carcinoma [29] .…”
Section: Discussionmentioning
confidence: 99%
“…In the prostates of rodents, it may be present in high concentration and is localised to prostate epithelium (Harper and Thoenen, 1980;Shikata et al, 1984;MacGrogan et al, 1990). Recently, MacGrogan et al have found f,-NGF expression and variable ,B-NGF concentrations (0-1720 pg g-') in human benign hyperplastic (BPH) tissue (MacGrogan et al, 1992).…”
mentioning
confidence: 99%
“…p75NTR exhibits a partial loss of expression during malignant transformation of the prostate and is almost totally lost in most prostate cancer cell lines (30,31). However, the p75NTR gene remains intact in these cells, indicating that the potential for up-regulation still exists (11,32). Inducing or re-expressing this receptor in prostate cancer cells can induce cell cycle arrest and may facilitate apoptosis (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that neurotrophins stimulate cell proliferation in androgenrefractory prostate cancer cell lines (10), exerting their effects by binding to the corresponding receptors (11). There are two types of neurotrophin receptors present in the prostate, the proto-oncogene tyrosine receptor kinase trkA and the 75-kDa glycoprotein p75NTR, which is a member of the TNF receptor superfamily.…”
Section: Introductionmentioning
confidence: 99%